Child Diet and Household Characteristics Relate Differently to Child Development at the Beginning and the End of the Second "1000 Days" in Rural Nepal. Issue 1 (March 2021) - Miller, Laurie C.; Neupane, Sumanta; Joshi, Neena; Lohani, Mahendra; Thorne-Lyman, Andrew
The "second 1000 days" is a period of rapid brain growth which consolidates developmental foundations and establishes school readiness. Understanding the relation between household characteristics, child diet, and child development remains incomplete, especially in resource-poor settings where >250 million children risk not achieving their full developmental potential. Child developmental performance was assessed (Ages & Stages Questionnaire [ASQ]) at ages 2 and 5 years in a cohort of Nepali children (n = 207) whose families participated in a nutrition/livestock management+community development intervention trial. Relationships between child developmental performance and mother's education, family wealth, child diet (animal source food [ASF] consumption, dietary diversity score [DDS]), school attendance, and intervention group were examined by adjusted linear regressions. These relationships varied at the 2 ages. At age 2 years, ASQ scores related positively to "Full Package Intervention" and negatively to "Partial Package Intervention" membership. At age 5 years, intervention group did not relate to ASQ scores. Mother's education did not relate to developmental findings for 2-year-olds. Mother's education, wealth, and school attendance positively predicted ASQ scores for these same children as 5-year-olds. Animal source food consumption was related to child development more strongly at age 5 than at 2 years. DDS had a less pronounced relationship to development than ASF consumption at both ages. Over this time span bracketing the second 1000 days, household characteristics and child diet related differentially to developmental performance depending on child age. Better understanding of the timing and mechanisms of these relationships is needed to effectively design interventions targeting improved child development in resource-poor settings.